Visualizando a guerra: arte e cultos odínicos na Escandinávia dos séculos VI ao XI - Silva, Monicy Araujo (2025)
Alongside the martial aspect and religious issues, art and figurations are undoubtedly the most discussed and analyzed characteristics about Scandinavia. Being an area rich in images, ranging from cave paintings, through illustrated stones, which are exclusive to the island of Gotland, and runic stones, we reach three-dimensional metal figures and images made in metal, iron, gold and bronze, such as the bracteates that, here, will be the object of analysis, as well as the others mentioned. Although all of Scandinavia is richly illustrated, in the research done on the subject, some periods are more present than others, either due to their relevance to the research or due to the few images obtained from a given period and, in the present research, we are making a cut that goes from the 6th century to the 11th century. The analysis of material remains, and Ancient Nordic Religions involves different interests and intentions that each author intends with their research. In this research, we seek to understand the representation of warriors and the religious or ritual context in which these images were made and disseminated, because even though these images are not direct expressions of reality, we understand that they help us understand the nuances of these religions and we can understand the use made of these objects. To construct this research, we started from the hypothesis that the representations of warriors in the monuments and artifacts are related to the religious and ritual context, furthermore, these representations are linked to real battle rites, demonstrating a martial link with the god Óðinn , and also as a secondary hypothesis, of the present research, we understand that the figurations show other aspects of the Odinic cult. Based on these hypotheses, the present research has as its main objective to understand the forms of representation of warriors and the religious or ritual context in which the images were made and disseminated. As a secondary objective, to analyze the religious and warrior aspects in art and archaeological findings, demonstrating a martial link with animal spirits and the god Óðinn, revealing another important aspect of Pre-Christian Nordic Religions focused on war.